ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA PADA DINAS SOSIAL PROVINSI NTT - Erwin A. D. Koroh; Wilsna Rupilu; Eugenia Hendrini P Tanan (JAKA - Jurnal Jurusan Akuntasi, 2021)
This study aims to determine "How do the budget planning documents, Human Resources (HR) and the procurement of goods and services partially or simultaneously affect the absorption of the budget at the social service office of the province of NTT?" This research is causality research and the data source used is primary data. Data collection techniques were carried out by distributing questionnaires to respondents. Data analysis in this study used multiple linear regression with the help of the SPSS (Statistical Package Of Social Science) program. The results of this study indicate that there is a positive and significant influence of planning factors and human resources on the absorption of the budget at the Social Service Office of the Province of NTT, while the procurement of goods and services has a positive correlation but does not significantly affect the absorption of the budget at the Social Service Office of the Province of NTT. Thus, it can be said that planning, human resources and procurement of goods and services simultaneously affect the absorption of the budget